Siomay Production with The Addition of Tilapia (Oreochromis Niloticus) Bone Meal - Panjaitan, Pola S.T.; Aripudin, Aripudin; Yuliawati, Indri; Nurpalah, Siti (PELAGICUS, 2023)
Fish bone meal is a product by preserving the fish bone in dry form followed by milling it into powder. Siomay is a food originating from China which is usually served by steaming or frying. This food is usually enjoyed along with tea (yam cha). Siomay, as one type dimsum is widely sold in Chinese restaurants and street vendors in Indonesia. The processing steps of making siomay with the addition of tilapia fish bone meal (Oreochromis niloticus) such as receiving of raw material, separating the bones from the meat, washing 1, boiling the fish bones, cutting the bones, drying the bones, grinding the bones, sieving the fish bone meal, kneading, molding followed by steaming and draining. The aim of this study was to describe the process of making siomay with the addition of tilapia fish bone and to describe the hedonic value and proximate value with different formulations. Formulations of fish bone meals were divided into four groups such as F1 (as a control), without any addition of fish bone meal, F2 6%, F3 7% and F4 12%. The hedonic values showed the panellists mostly liked the formulation of F1 with the addition of 6% of fish bone meal. Characteristics of proximate values of F1 resulted in the water content being 66.95%, fat content being 4.5%, protein content being 5.35% and ash content being 5.77%.